2007
DOI: 10.1242/dev.002642
|View full text |Cite
|
Sign up to set email alerts
|

The generation of adipocytes by the neural crest

Abstract: Fat cells (adipocytes) develop from adipocyte precursor cells (preadipocytes) that themselves derive from mesenchymal progenitors. Although the events controlling preadipocyte differentiation into mature adipocytes have been largely explored, the mechanisms that direct mesenchymal progenitors down the adipocyte pathway remain unknown. Similarly, although adipocytes are generally thought to derive from mesoderm, key information is lacking regarding the origin and the development of the adipose tissue during emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 75 publications
11
193
1
10
Order By: Relevance
“…Our data show that NC-derived adipocytes form a well-defined subcutaneous fat depot in the cervical region of adult WNT1-Cre/R26-YFP mice, confirming previous data reporting the presence of NCderived adipocytes surrounding the salivary gland in adult Sox10-Cre/R26-YFP mice [5]. Furthermore, neural-crestderived adipocytes accumulate ectopically during fatty infiltration of craniofacial muscles, accounting for 70% of the adipocytes generated following degenerative damage of the masseter in 5-week-old mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data show that NC-derived adipocytes form a well-defined subcutaneous fat depot in the cervical region of adult WNT1-Cre/R26-YFP mice, confirming previous data reporting the presence of NCderived adipocytes surrounding the salivary gland in adult Sox10-Cre/R26-YFP mice [5]. Furthermore, neural-crestderived adipocytes accumulate ectopically during fatty infiltration of craniofacial muscles, accounting for 70% of the adipocytes generated following degenerative damage of the masseter in 5-week-old mice.…”
Section: Discussionsupporting
confidence: 92%
“…Previous data have indicated a role for the NC in the generation of white adipose tissue (WAT), one of the major mesenchymal lineages [5]. While the mesoderm has long been considered the only source of WAT, certain forms of WAT dystrophies, such as congenital infiltrating lipomatosis of the face (CIL-F) [6,7] and the Dunnigan-Kobberling syndrome [8] suggest the existence of different cellular mechanisms for cephalic versus trunk and limb adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some neck WAT depots are colonised by neural crest cells (Billon et al 2007), migratory multipotent cells from the dorsal neural tube, but very little is known about the origins and signals that regulate WAT adipocyte formation. As a result, there are also fewer well-established molecular markers of specific developmental stages of adipocyte cell formation available to inform studies of adipose development.…”
Section: Evidence For Programming Of Body Fatmentioning
confidence: 99%
“…However, lineage-tracking studies have shown that at least a subset of adipocytes originates from MSCs derived from the neuroectoderm. 27 Comprehensive lineage-tracking studies are required to clarify this question, but a mixed origin of the different fat deposits would explain their distinctive molecular and biological features. 18,21 An extracellular cue recruits MSCs to commit to a particular lineage (Fig.…”
Section: The Adipose Tissuementioning
confidence: 99%